Electric field effects on β-lactoglobulin thermal unfolding as a function of pH – Impact on protein functionality. (March 2019) - Rodrigues, Rui M.; Vicente, António A.; Petersen, Steffen B.; Pereira, Ricardo N.
Abstract: The presence of moderate electric fields (MEF) during ohmic heating (OH) treatment of whey protein systems have demonstrated potential to change physicochemical and functional properties, like aggregation rate and extension or viscoelastic behaviour. However, the specific action of MEF upon the molecular structure of proteins, particularly during thermal processing has yet to be clarified. The effects of MEF in pure fractions of β-lactoglobulin (β-lg) under non-aggregating conditions (low concentration and ionic strength), were investigated in this work. Protein samples were identically heat-treated through conventional and OH methods and at different pH values. β-lg's structural features were characterized by evaluation of secondary structure distribution and local conformational changes using techniques such as circular dichroism, intrinsic and extrinsic fluorescence and free thiol groups reactivity. It was confirmed that MEF affects β-lg upon thermal unfolding, resulting in distinctive structural features, surface hydrophobicity and SH reactivity. The mechanism of action is probably related with the molecular motion induced by the oscillating electric field and is more pronounced at neutral pH, where β-lg is more susceptible to thermal structural changes. These results contribute to a better understanding of OH processing and its effects in food matrices reinforce the possibility of using MEF as a toll to change protein functionality. Industrial relevance: Ohmic heating is an emerging technology and is being established as reference method for processing protein-rich food such as dairy and egg products. Non-thermal effects of the applied electric fields during ohmic heating have been addressed but few works deal with their real impact in structural and molecular properties of food proteins with high biological value. In this work demonstrated that the presence of an electric field during ohmic heating processing influences structural aspects of beta-lactoglobulin. This knowledge plays an important role on process design (i.e. pasteurization binomials and fouling control) and product quality because these proteins play an essential role in food's nutritional and organoleptic properties, as well as on functionality, allergenicity and stability aspects. Highlights: The effects of ohmic heating on the unfolding of β-lg was evaluated from 50 to 90 °C and pH 3 to 7 The presence of moderate electric fields during ohmic heating have demonstrated to affect β-lg conformation upon unfolding. MEF results in different structural features, hydrophobic and sulfhydryl reactivity profiles, affecting protein functionality β-lg ´s response to thermal and electric effects is dependent of the pH and is more marked at neutral pH